1970
DOI: 10.5424/sjar/20110904-069-11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arbuscular mycorrhizal fungi and an improving growth bacterium on Cd uptake and maize growth in Cd-polluted soils

Abstract: In a pot experiment, the effects of the bacterium strain Micrococcus roseus, native soil arbuscular mycorrhizal fungi (AMF) and the fungus Glomus mosseae on the growth, P, N, Fe, Mn, Zn and Cd uptake of maize in a soil polluted with Cd were investigated. A three-factor experiment was set up in a randomized complete design with three replicates of each treatment. The factors in the experiment were as follows: 1) AMF with two levels, G 1 (native AMF) and G 2 (G. mosseae + G 1 ); 2) bacterium promoting plant grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The results also indicated that Cd and Zn toxicity had no negative effect on root colonization of plants with AM fungi interaction as compared to plants with no fungal interaction. The same results were reported by [28] [29]. The growth inhibition in plants grown under high levels of Zn and Cd was due to interference of these metals with P uptake by plants.…”
Section: Effect Of Amf Inoculation On Alfalfa Growth Biomass and Colsupporting
confidence: 85%
“…The results also indicated that Cd and Zn toxicity had no negative effect on root colonization of plants with AM fungi interaction as compared to plants with no fungal interaction. The same results were reported by [28] [29]. The growth inhibition in plants grown under high levels of Zn and Cd was due to interference of these metals with P uptake by plants.…”
Section: Effect Of Amf Inoculation On Alfalfa Growth Biomass and Colsupporting
confidence: 85%
“…This study used indigenous AMF, which were associated with indigenous ferns in the gullies and few grasses on the plateau of the mined-out areas. Several studies demonstrated the effectiveness of indigenous AMF in stimulating plant growth in heavy metal contaminated sites (Gildon and Tinker 1983;Diaz et al 1996;Cabello 1999;Malekzadeh et al 2011). Some studies had reported otherwise (Enktuya et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal fungi can achieve morphological transformation of trace elements in the rhizosphere soil through various pathways, in-cluding chemical precipitation in the soil through acidification and immobilization [44]. The AMF could improve plant tolerance to metals by different mechanisms such as (1) metal restriction by compounds (e.g., glomalin) secreted by AMF [45], Qiu et al [46] found that the significant negative correlation between GRSP and the combined indicators of eight bioavailable metals' concentration, (2) accumulation of metals on the hyphal surface [47], metal adsorption onto substance (e.g., chitin) in the cell walls [48], to reduce the metals translocation to the host plant, (3) AMF increases the content of phosphorus in the soil, metal deposition in polyphosphate particles in the soil [49,50], (4) alteration of metals availability by changing the rhizosphere pH [51], (5) regulation of gene expression under stress conditions [52], AMF symbiosis up-regulated metallothionein PtMT2b in roots regardless of contamination, PtMT2b greatly increased Cd tolerance in transgenic yeast under Cd stress [53], AMF colonization distinctly reduced the level of MsPCS1 and MsMT2 genes, thereby reducing Cd translocation to the aboveground biomass [54]. One study has demonstrated a significant increase in the biomass of AMF-inoculated plants in soils contaminated with Cd.…”
Section: Improving Metal Tolerance In Plantsmentioning
confidence: 99%